Determinants of secondary traumatic stress in midwives: The role of workplace-related factors - Maryam Hajiesmaello; Sepideh Hajian; Hedyeh Riazi; Hamid Alavi Majd; Roya Yavarian (Nursing and Midwifery Studies)
Background: Secondary traumatic stress (STS) among midwives is a critical concern that can lead to emotional distress and adversely affect maternal and newborn care.Objectives: This study aimed to assess the prevalence and severity of STS, along with its determinants, among midwives employed in labor and delivery departments in West Azerbaijan, Iran.Methods: This cross-sectional study included all midwives working in labor and delivery departments across 18 hospitals and four rural midwifery service facilities from April 2020 to January 2021. Data were collected using demographic questionnaires, the Secondary Traumatic Stress Scale, and various job-related questionnaires. Statistical analyses, including analysis of variance and multiple linear regression, were performed using SPSS software version 23. Additionally, path analysis was conducted using Amos software version 24 to evaluate the direct and indirect determinants of STS prevalence.Results: A total of 349 midwives participated, with a mean work experience of 6.88 ± 6.44 years. Among the participants, 45% reported mild to moderate levels of STS, while 37.5% experienced severe STS. Path analysis revealed that the intention to remain in the midwifery profession had a direct protective effect against STS (β=0.184, P=0.009). Conversely, psychological distress resulting from workplace violence and adverse behaviors (β=0.361, P=0.007) and job burnout (β=0.260, P=0.003) were found to increase the risk of STS both directly and indirectly.Conclusion: In addition to exposure to traumatic events, workplace-related factors significantly contribute to the development of STS in midwives. It is essential for midwives working in labor and delivery departments to receive adequate support from the Ministry of Health and relevant medical organizations.